Ecological, topographic and successional patterns across wetlands in a rugged land uplift coast in Nyby, northern Finland - Laitinen, Jarmo; Oksanen, Jari; Maliniemi, Tuija; Kaakinen, Eero; Aapala, Kaisu; Rehell, Sakari (Geographical Society of Finland, 2016)
We studied 45 mid-boreal wetlands in a rugged land uplift coast with a thin cover of till. Wetlands ranged from 1 to 53 m a.s.l. and were of highly various sizes. Our aims were to examine, if vegetation types are valid in comparing wetlands, what kind of ecological major pattern the vegetation type composition of wetlands shows and how vegetation types distribute across altitudes. On those ground we discuss the wetland succession of the study area. We used the Finnish mire site types as vegetation types. Mire site types could be used for an ecological classification and ordination of the wetlands. As was expected, the major gradient consisted of the transition from mire margin (swamp) to expanse. The distribution of the Major Vegetational Wetland Groups (MVWG) responded to a general water-flow pattern in the landscape. Partly different peatland succession sequences occur in areas with small mire basins and in areas with larger mire basins with evolving mire complexes. Sequences of small wetlands and those of mire complexes follow the same trajectory only as far as the major gradient is considered while they differ with regard to the vegetation type composition of locally rare vegetation types and with regard to peatland morphology. Trajectories of mire complexes at catchment divides differ from those at catchment centers where the waters in the landscape tend to gather. Peatland forms of aapa mires experience a change reaching altitudes of 30–50 m a.s.l. Small bog complexes at catchment divides reach a stage of an unpatterned Sphagnum fuscum bog in the study area. Mature mixed complexes with aapa-mire parts and patterned sloping-bog parts only occur at altitudes higher than 60 m a.s.l. Peculiarities in the succession of the wetlands of Nyby, which include the presence of separate incomplete successional sequences in the same area, are mainly caused by the peculiar topography with various sub-areas and with an abundance of rock outcrops.